Stakeholder Pressure, Well-Being, and the Mediating Role of Innovation Capability in Batik Artisan Entrepreneurship in Madura - Uswatun Hasanah; Arnani, Ni Putu Rizky (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of stakeholder pressure on innovation capability and well-being among batik artisan entrepreneurs in Madura. Using a quantitative approach and purposive sampling of 100 artisans, results show stakeholder pressure positively affects both innovation capability and well-being. However, innovation capability negatively affects well-being. These findings indicate innovation plays a dual role: it is essential for competitive advantage but may reduce well-being if poorly managed. The study suggests balancing innovation with well-being support to sustain artisan entrepreneurship and cultural heritage in dynamic business environments.